Pengaruh Konseling Gizi Terhadap Pengetahuan dan Tingkat Konsumsi Zat Gizi Makro dan Zat Gizi Mikro pada Pasien Tuberkulosis Paru di UPT Rumah Sakit Khusus Paru Provinsi Sumatera Utara - Eka Nenni Jairani; Bertha Nurlina Napitupulu; Rani Suraya; Wanda Lestari; Yulita Yulita; Agnes Sry Vera Nababan (Jurnal Riset Hesti Medan, 2022)
The highest TB morbidity and mortality rates are in developing countries, including Indonesia. WHO hopes that TB research conducted in all countries can provide scientific evidence that it is important for all TB patients to be assessed for nutritional status and given nutritional counseling in all health facilities and the need to set operational standards in the treatment of malnutrition due to TB. The aimed of this study was to determine the effect of nutritional counseling on knowledge of carbohydrate, protein, vitamin A and zinc intakes in pulmonary TB patients at Unit Pulmonary Hospital of North Sumatra Province. This research was carried out at Special Pulmonary Hospital, North Sumatra Province. It was conducted in August - September 2021. This research was a Quasi Experimental study with One Group Pre and Post test Design. The population were all outpatient pulmonary TB patients with positive smear sputum in the DOTS poly in Unit Pulmonary Hospital of North Sumatra Province and the sample was 60 people who met the inclusion criteria. Obtained are that through the statistical tests, showed that the counseling carried out had a significant effect on increasing knowledge (p=0.000), carbohydrate intake (p=0.001), protein intake (p=0.000), vitamin A intake (p=0.000) and zinc mineral intake (p=0.000). It is hoped that this study can provide information for pulmonary TB patients about nutritional counseling in changing the intake of good nutrients to accelerate healing and suppress transmission of pulmonary TB.